RNA-Based Fluorescent Biosensors for Live Cell Imaging of Second Messenger Cyclic di-AMP - Kellenberger, Colleen A; Chen, Chen; Whiteley, Aaron T; Portnoy, Daniel A; Hammond, Ming C (Journal of the American Chemical Society, 2015)
Cyclic di-AMP (cdiA) is a second messenger predicted to be widespread in Gram-positive bacteria, some Gram-negative bacteria, and Archaea. In the human pathogen Listeria monocytogenes, cdiA is an essential molecule that regulates metabolic function and cell wall homeostasis, and decreased levels of cdiA result in increased antibiotic susceptibility. We have generated fluorescent biosensors for cdiA through fusion of the Spinach2 aptamer to ligand-binding domains of cdiA riboswitches. The biosensor was used to visualize intracellular cdiA levels in live L. monocytogenes strains and to determine the catalytic domain of the phosphodiesterase PdeA. Furthermore, a flow cytometry assay based on this biosensor was used to screen for diadenylate cyclase activity and confirmed the enzymatic activity of DisA-like proteins from Clostridium difficile and Methanocaldococcus jannaschii. Thus, we have expanded the development of RNA-based biosensors for in vivo metabolite imaging in Gram-positive bacteria and have validated the first dinucleotide cyclase from Archaea.